Effect of silicon rate and host resistance on blast, scald, and yield of upland rice - Seebold, KW; Datnoff, LE; Correa Victoria, Fernando J.; Kucharek, TA; Snyder, GH (Scientific Societies, 2000)
Blast-resistant, partially resistant, and susceptible cultivars of rice were planted in soil amended with Si at 0, 500, or 1,000 kg/ha at two locations in eastern Colombia to assess differential responses to leaf blast, neck blast, and leaf scald, and to examine the quantity and quality of grains harvested. Leaf and neck blast on partially resistant and susceptible cultivars were reduced by Si as the rate of Si was increased. Depending on the location, the level of severity of leaf and neck blast on partially resistant cultivars, when fertilized with Si at 500 or 1,000 kg/ha, was lowered to that of resistant cultivars without Si. At both locations, yields were increased by as much as 42%, depending on the cultivar, by Si applied at 1,000 kg/ha. In general, high rates of Si reduced the number of broken grains harvested. Grain discoloration, regardless of cultivar or location, was reduced by as much as 70% at the high rate of Si. The application of Si to complement host resistance to blast and scald appears to be an effective strategy for disease management in rice and provides the added benefit of improving the quantity and quality of rice yields.